2022
DOI: 10.3390/healthcare10071227
|View full text |Cite
|
Sign up to set email alerts
|

Marital Satisfaction and Perceived Family Support in Families of Children with Autistic Spectrum Disorder: Dyadic Analysis

Abstract: Background: Raising children with autism spectrum disorder (ASD) causes tremendous stress for parents that may lead to marital conflict and relationship dissatisfaction. Many factors are associated with parent relationships including severity of autistic behaviors and social support. This study aimed to investigate whether severity of autistic behaviors, perceived family support, and complementarity of interpersonal styles between husbands and wives predicted couple satisfaction among the parents of children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
7
0
2
Order By: Relevance
“…The longer the time spent by the wives had no effect on their relationship with their husbands; in fact, the time wives spent on their children also made their husbands dissatisfied. This can be explained by the fact that the husbands were unhappy because the wives spent so much time with their children, resulting in husbands feeling neglected [43]. Also, the Gagat-Matuła (2021) study conducted in the COVID-19 pandemic among married couples with a child with ASD, showed that spouses more often prefer non-constructive coping with stress using the emotion-focused style (SSE) or the avoidance-focused style (SSU) if the spouses assesses both themselves and their spouse as depressed.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer the time spent by the wives had no effect on their relationship with their husbands; in fact, the time wives spent on their children also made their husbands dissatisfied. This can be explained by the fact that the husbands were unhappy because the wives spent so much time with their children, resulting in husbands feeling neglected [43]. Also, the Gagat-Matuła (2021) study conducted in the COVID-19 pandemic among married couples with a child with ASD, showed that spouses more often prefer non-constructive coping with stress using the emotion-focused style (SSE) or the avoidance-focused style (SSU) if the spouses assesses both themselves and their spouse as depressed.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Also, the Gagat-Matuła (2021) study conducted in the COVID-19 pandemic among married couples with a child with ASD, showed that spouses more often prefer non-constructive coping with stress using the emotion-focused style (SSE) or the avoidance-focused style (SSU) if the spouses assesses both themselves and their spouse as depressed. The greater the difference between their own assessment and the assessment of their spouse in supportive communication, the more often the respondents prefer the style focused on emotions (SSE) and the style focused on avoidance (SSU) [43].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Ademais, existem indicações de que os pais com dificuldades financeiras apresentaram pontuações mais altas de depressão e ansiedade em comparação com aqueles sem dificuldades financeiras. Por isso a importância de intervenções que se concentrem tanto nos aspectos negativos (problemas emocionais e comportamentais das crianças, necessidades de apoio não satisfeitas dos pais) como positivos (satisfação no relacionamento conjugal dos pais) do cuidado de crianças com TEA (Khusaifan e Keshky, 2022;He et al, 2022).…”
Section: Discussionunclassified
“…Parents of children with NDDs were found to be at increased risk of conflicting and unsatisfied relationships. 46 48 Satisfactory family and marital environment are linked to low expressed emotion. In contrast, extreme family conflicts were linked to high expressed emotion.…”
Section: Discussionmentioning
confidence: 99%